Bridgs to academy writing - Strauch, Ann O. (New York: Cambridge University Press, 1998)
Contents: 1. blends an in-depth process approach with organizational pattems such as narration, reassons, summary and response, 2. offers flexibility in the presentation of the material, 3. progress from more controlled to less contralled tasks, 4. contains a broad selection of engaging readings for summary- and response assigments...
Keywords: Sistema de Escritura